Upaya Meningkatkan Keaktifan dan Hasil Belajar Melalui Model Problem Based Learning pada Materi Sistem Injeksi (Lembag, 2026)
This study aims to improve students’ learning activities and learning outcomes through the implementation of the Problem Based Learning (PBL) model in the fuel injection system material for twelfth-grade Ototronik students. The background of this research is the low level of student participation and learning outcomes in the classroom. This research employed Classroom Action Research with two cycles involving 34 students. Data were collected using observation sheets to measure students’ learning activities and tests to assess learning outcomes. The results showed a significant improvement in both aspects. In the first cycle, 73.52% of students demonstrated active participation, which increased to 97.02% in the second cycle. Meanwhile, students’ average learning outcomes improved from 65.15 in the pre-cycle to 72.20 in the first cycle and reached 77.35 in the second cycle. These findings indicate that the implementation of the PBL model effectively enhances student engagement and academic achievement. Therefore, the PBL model can be used as an alternative teaching strategy to improve learning quality in vocational education, particularly in automotive subjects.